Parallel vs perspective projection in computer graphic / Intan Syaherra Ramli - Ramli, Intan Syaherra (Universiti Teknologi MARA, Negeri Sembilan, 2022)
In computer graphics, projective transformation is one of the crucial aspects to understand the image transformation. This phase is part of the three-dimensional (3D) viewing pipeline after the object description has been transferred to the viewing-coordinates reference frame. The conversion of object description can be accomplished using translation and rotation between viewing and world coordinate. After that, the object description is projected to the view plane with parallel or perspective projection. In parallel projection, the coordinate positions are transferred to the view plane along with the parallel line. Meanwhile, in the perspective projection, the object projection is transformed to the view plane along the lines that converge to a point behind the view plane.